2014
DOI: 10.1111/liv.12625
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare‐associated and nosocomial bacterial infections in cirrhosis: predictors and impact on outcome

Abstract: In a population-based cirrhotic cohort, two-thirds of serious bacterial infections were HCA or HA. Decompensated liver disease, antibiotics and PPIs were predictors of serious HCA/HA infections, which were associated with the development of ACLF. Antibiotic resistance was frequent, especially in HA infections, and contributed to risk of severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 38 publications
7
34
0
Order By: Relevance
“…In any case, subsequent infections occurring within 6 months after discharge after the index hospitalization (ie, all infections registered during follow-up evaluation in the study 1 ), would be considered HCA (or HA if they occurred >48 h after hospital admission), 3 and thus the presented data, which suggest a relationship between PPI use and subsequent HCA/HA infections, seem to be consistent with our findings. 2 Taken together, the findings of O'Leary et al 1 and those of our study 2 suggest that the use of PPIs is a predictor of subsequent HCA/HA infections after discharge after hospitalization for a bacterial infection. As O'Leary et al 1 pointed out in their article, the observed associations between PPI use and subsequent HCA/HA infections do not necessarily imply a causal link.…”
Section: Subsequent Bacterial Infections In Patients With Cirrhosis Asupporting
confidence: 79%
See 3 more Smart Citations
“…In any case, subsequent infections occurring within 6 months after discharge after the index hospitalization (ie, all infections registered during follow-up evaluation in the study 1 ), would be considered HCA (or HA if they occurred >48 h after hospital admission), 3 and thus the presented data, which suggest a relationship between PPI use and subsequent HCA/HA infections, seem to be consistent with our findings. 2 Taken together, the findings of O'Leary et al 1 and those of our study 2 suggest that the use of PPIs is a predictor of subsequent HCA/HA infections after discharge after hospitalization for a bacterial infection. As O'Leary et al 1 pointed out in their article, the observed associations between PPI use and subsequent HCA/HA infections do not necessarily imply a causal link.…”
Section: Subsequent Bacterial Infections In Patients With Cirrhosis Asupporting
confidence: 79%
“…However, second HCA/HA infections occurred more frequently after a first inpatient HCA/HA infection episode in PPI users ( Figure 1B), in particular, in those with more than 1 daily defined dose of PPIs (P ¼ .019). 2 Unfortunately, it is unclear what the proportions of the different acquisition types of the index infections in the cohort of O'Leary et al 1 were because these were not presented in their article. In any case, subsequent infections occurring within 6 months after discharge after the index hospitalization (ie, all infections registered during follow-up evaluation in the study 1 ), would be considered HCA (or HA if they occurred >48 h after hospital admission), 3 and thus the presented data, which suggest a relationship between PPI use and subsequent HCA/HA infections, seem to be consistent with our findings.…”
Section: Subsequent Bacterial Infections In Patients With Cirrhosis Amentioning
confidence: 95%
See 2 more Smart Citations
“…10,11 Frequent need for hospitalization, invasive procedures and, use of indwelling devices such as central venous line or transjugular intrahepatic portosystemic shunt (TIPS), give to the exogenous route an additional pathogenetic rule, further increasing the overall risk, mainly in the setting of Health Care Associated or Hospital Acquired infections. 12,13 BSIs in LC are also associated with high mortality, prolonged hospitalization and faster escalation of the liver disease. 14,15 In different studies including both cirrhotic and non-cirrhotic patients with bacteriemia or candidemia, LC was found to be an independent predictor of mortality.…”
Section: Introductionmentioning
confidence: 99%